A new microwave dielectric material LiNi0.5Ti0.5O2. Issue 7 (August 2015) - Lyu, Xiaosong; Li, Lingxia; Cai, Haocheng; Sun, Hao
Abstract: A new low-loss LiNi0.5 Ti0.5 O2 ceramic was prepared by the conventional solid-state reaction route and its microwave dielectric properties were investigated. Single phase LiNi0.5 Ti0.5 O2 was obtained and it showed rock salt structure. The microstructures of the ceramics were characterized by SEM. The variation trends of dielectric constant and Q × f value were in accordance with variation trends of relative density and the grain morphology. Further, the τ f value was insensitive to sintering temperature. The following typical values ε r ~19.25, Q × f ~51290 GHz, τ f ~−20.1 ppm/°C were obtained for LiNi0.5 Ti0.5 O2 (1275 °C/6 h). The microwave dielectric properties of the ceramic are reported for the first time.